Prenatal and lactational nitrate exposure in drinking water induces modest alterations in offspring sensorimotor development, physiology and adult locomotor activity in a rat model - Leaf R. Kardol; Avalon Gray; Alexander N. Larcombe; Christine Jeffries-Stokes; Annette Stokes; Sarah Bourke; Sujata Shinde; Kevin Croft; Caitlin S. Wyrwoll (Environmental Pollution, 2026)

On‐Farm Demonstration and Economic Evaluation of an IoT Sensing System for Irrigation Management in South Carolina - J. O. Payero; U. Sekaran; D. B. Turner; S. Selvalakshmi; M. W. Marshall; N. Smith; J. Croft; A. S. Hill; R. Hitchcock‐Davis (Irrigation and Drainage, 2026)
Irrigation can strongly influence agricultural productivity and sustainability. While sensor‐based irrigation has the potential to improve yield, reduce input costs and enhance resource‐use efficiency, its adoption in commercial agriculture remains limited. This study evaluated and demonstrated the performance of an IoT soil water monitoring system and the effects of sensor‐based irrigation on crop yield and economic returns in commercial farms in South Carolina. Field demonstrations were conducted across 18 site‐year observations (six farms annually from 2020–2022) under centre pivot systems. The centre pivot fields for each farm were divided into sensor fields and companion fields. The sensor fields used soil water potential (SWP) data from sensors installed at multiple depths to guide irrigation, while irrigation in the companion field followed farmers' preferred practices. Data collected from each site included irrigation applied, pumping characteristics, energy use, yield and economic returns. The IoT monitoring system reliably collected and transmitted data across all locations and years. Despite variability, the sensor fields achieved average increases of 11% in yield and 12% in net economic return compared with companion fields. These results indicate that sensor‐based irrigation improves water management and profitability under commercial conditions, supporting broader adoption of these technologies.

Synergies between potential key geoheritage areas (KGAs) and key biodiversity areas (KBAs) in Spain and Scotland: Toward a holistic nature conservation framework - M.R. Monge-Ganuzas; J.E. Gordon; R. Crofts; D. Juffe Bignoli; J.B. Brilha (Journal for Nature Conservation, 2026)

Prolonged exposure to nitrate in drinking water does not adversely impact prenatal or birth outcomes in a rat model - Leaf R. Kardol; Avalon Gray; Amina Rhaman; Alexander N. Larcombe; Christine Jeffries-Stokes; Annette Stokes; Sarah Bourke; Sujata Shinde; Kevin Croft; Caitlin S. Wyrwoll (Regulatory Toxicology and Pharmacology, 2026)

Exposure to radiofrequency electromagnetic fields and IARC carcinogen assessment: Risk of Bias preliminary literature assessment for 10 key characteristics of human carcinogens - Myrtill Simkó; Michael H. Repacholi; Kenneth R. Foster; Mats-Olof Mattsson; Rodney J. Croft; Maria Rosaria Scarfi; Vijayalaxmi (Mutation Research - Reviews in Mutation Research, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Modelling the continuum of macrophage phenotypes and their role in inflammation - Suliman Almansour; Joanne L. Dunster; Jonathan J. Crofts; Martin R. Nelson (Mathematical Biosciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

High frequency UV–Vis sensors estimate error in riverine dissolved organic carbon load estimates from grab sampling - J. P. Ritson; O. Kennedy-Blundell; J. Croft; M. R. Templeton; C. E. Hawkins; J. M. Clark; M. G. Evans; R. E. Brazier; D. Smith; N. J. D. Graham (Environmental Monitoring and Assessment, 2022)
High frequency ultraviolet – visible (UV–VIS) sensors offer a way of improving dissolved organic carbon (DOC) load estimates in rivers as they can be calibrated to DOC concentration. This is an improvement on periodic grab sampling, or the use of pumped sampling systems which store samples in-field before collection. We hypothesised that the move to high frequency measurements would increase the load estimate based on grab sampling due to systemic under-sampling of high flows. To test our hypotheses, we calibrated two sensors in contrasting catchments (Exe and Bow Brook, UK) against weekly grab sampled DOC measurements and then created an hourly time series of DOC for the two sites. Taking this measurement as a ‘true’ value of DOC load, we simulated 1,000 grab sampling campaigns at weekly, fortnightly and monthly frequency to understand the likely distribution of load and error estimates. We also performed an analysis of daily grab samples collected using a pumped storage sampling system with weekly collection. Our results show that: a) grab sampling systemically underestimates DOC loads and gives positively skewed distributions of results, b) this under-estimation and positive skew decreases with increasing sampling frequency, c) commonly used estimates of error in the load value are also systemically lowered by the oversampling of low, stable flows due to their dependence on the variance in the flow-weighted mean concentration, and d) that pumped storage systems may lead to under-estimation of DOC and over estimation of specific ultra-violet absorbance (SUVA), a proxy for aromaticity, due to biodegradation during storage.

A New Glyptodont (Xenarthra: Cingulata) from the Late Miocene of Argentina: New Clues About the Oldest Extra-Patagonian Radiation in Southern South America - Daniel Barasoain; Alfredo E. Zurita; Darin A. Croft; Claudia I. Montalvo; Víctor H. Contreras; Ángel R. Miño-Boilini; Rodrigo L. Tomassini (Journal of Mammalian Evolution, 2022)

Comparative Endocranial Anatomy, Encephalization, and Phylogeny of Notoungulata (Placentalia, Mammalia) - Fernando A. Perini; Thomas E. Macrini; John J. Flynn; Kanvaly Bamba; Xijun Ni; Darin A. Croft; André R. Wyss (Journal of Mammalian Evolution, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

New Chinchillid Rodents (Hystricognathi: Caviomorpha) from Northern Chile and Bolivia Fill a 17-Million-Year Gap in the Pan-Chinchilline Fossil Record - Darin A. Croft; John J. Flynn; André R. Wyss; Reynaldo Charrier; Federico Anaya (Journal of Mammalian Evolution, 2021)

Wi-fi related radiofrequency electromagnetic fields (RF-EMF): a pilot experimental study of personal exposure and risk perception - Berihun M. Zeleke; Christopher Brzozek; Chhavi R. Bhatt; Michael J. Abramson; Frederik Freudenstein; Rodney J. Croft; Peter Wiedemann; Geza Benke (Journal of Environmental Health Science and Engineering, 2021)
The impact of providing people with an objectively measured personal radiofrequency electromagnetic fields (RF-EMF) exposure information on the risk perception of people is not well understood. We conducted an experimental study, among three groups of participants, to investigate the risk perception of people towards RF-EMF from Wi-Fi sources (ISM 2.4 GHz) by providing participants with either basic text, precautionary information, or a summary of their personal RF-EMF exposure measurement levels. Participants provided with personal RF-EMF exposure measurement information were more confident in protecting themselves from RF-EMF exposure, compared to those provided with only basic information. Nonetheless, neither the exposure perception nor the risk perception of people to Wi-Fi related RF-EMF differed by the type of information provided. The measured Wi-Fi signal levels were far below international exposure limits. Furthermore, self-rated levels of personal RF-EMF exposure perception were not associated with objectively measured RF-EMF exposure levels. Providing people with objectively measured information may help them build confidence in protecting themselves from Wi-Fi related RF-EMF exposure.

Hyperthermia, but not dehydration, alters the electrical activity of the brain - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Nigel A. S. Taylor; Rodney J. Croft (European Journal of Applied Physiology, 2020)

Hyperthermia and dehydration: their independent and combined influences on physiological function during rest and exercise - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Rodney J. Croft; Gregory E. Peoples; Nigel A. S. Taylor (European Journal of Applied Physiology, 2020)

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

First record of false killer whales (Pseudorca crassidens) in the Falkland Islands (Malvinas) - Sarah Crofts; Karen K. Martien; Kelly M. Robertson; Andrew Stanworth; Steve Massam; Caroline R. Weir (Polar Biology, 2019)

A numerical simulation of neural fields on curved geometries - R. Martin; D. J. Chappell; N. Chuzhanova; J. J. Crofts (Journal of Computational Neuroscience, 2018)

Effect of dietary nitrate supplementation on thermoregulatory and cardiovascular responses to submaximal cycling in the heat - Georgina L. Kent; Brian Dawson; Gregory R. Cox; Chris R. Abbiss; Kurt J. Smith; Kevin D. Croft; Zi Xiang Lim; Annette Eastwood; Louise M. Burke; Peter Peeling (European Journal of Applied Physiology, 2018)

Stress and welfare in ornamental fishes: what can be learned from aquaculture? - C. H. Stevens; D. P. Croft; G. C. Paull; C. R. Tyler (Journal of Fish Biology, 2017)
The ornamental fish trade is estimated to handle up to 1·5 billion fishes. Transportation and handling of fishes imposes a range of stressors that can result in mortality at rates of up to 73%. These rates vary hugely, however, and can be as low as 2%, because they are generally estimated rather than based on experimental work. Given the numbers of ornamental fishes traded, any of the estimated mortality rates potentially incur significant financial losses and serious welfare issues. Industry bodies, such as the Ornamental Aquatic Trade Association (OATA), have established standards and codes of best practice for handling fishes, but little scientific research has been conducted to understand the links between stress, health and welfare in ornamental species. In aquaculture, many of the same stressors occur as those in the ornamental trade, including poor water quality, handling, transportation, confinement, poor social and physical environment and disease and in this sector directed research and some resulting interventions have resulted in improved welfare standards. This review considers the concept of welfare in fishes and evaluates reported rates of mortality in the ornamental trade. It assesses how the stress response can be quantified and used as a welfare indicator in fishes. It then analyses whether lessons from aquaculture can be usefully applied to the ornamental fish industry to improve welfare. Finally, this analysis is used to suggest how future research might be directed to help improve welfare in the ornamental trade.

The independent influences of heat strain and dehydration upon cognition - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Nigel A. S. Taylor; Rodney J. Croft (European Journal of Applied Physiology, 2017)

Sexual response of male Drosophila to honey bee queen mandibular pheromone: implications for genetic studies of social insects - Justin R. Croft; Tom Liu; Alison L. Camiletti; Anne F. Simon; Graham J. Thompson (Journal of Comparative Physiology A, 2017)

Consequences of Fish Kills for Long-Term Trophic Structure in Shallow Lakes: Implications for Theory and Restoration - Carl D. Sayer; Thomas A. Davidson; Ruth Rawcliffe; Peter G. Langdon; Peter R. Leavitt; Georgina Cockerton; Neil L. Rose; Toby Croft (Ecosystems, 2016)

In photosynthesis, oxygen comes from water: from a 1787 book for women by Monsieur De Fourcroy - Pierre Joliot; Antony R. Crofts; Lars Olof Björn; Christine T. Yerkes; Govindjee (Photosynthesis Research, 2016)

Assessment of resistance to root-lesion and root-knot nematodes in Australian hybrid clones of sugarcane and its wild relatives - S. A. Bhuiyan; B. J. Croft; G. R. Stirling; E. Wong; P. Jackson; M. Cox (Australasian Plant Pathology, 2016)

Efficacy of the fungicide flutriafol for the control of pineapple sett rot of sugarcane in Australia - S. A. Bhuiyan; B. J. Croft; G. R. Tucker (Australasian Plant Pathology, 2014)

Temperature explains variable spread rates of the invasive woodwasp Sirex noctilio in the Southern Hemisphere - M. Victoria Lantschner; José M. Villacide; Jeffrey R. Garnas; Philip Croft; Angus J. Carnegie; Andrew M. Liebhold; Juan C. Corley (Biological Invasions, 2014)

Spatial proximity loggers for recording animal social networks: consequences of inter-logger variation in performance - N. K. Boyland; R. James; D. T. Mlynski; J. R. Madden; D. P. Croft (Behavioral Ecology and Sociobiology, 2013)

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

Multiseason evaluation of the MM5, COAMPS and WRF over southeast United States - Duanjun Lu; L. White; R. S. Reddy; Quinton L. Williams; Paul J. Croft (Meteorology and Atmospheric Physics, 2011)

ERP correlates of response inhibition after-effects in the stop signal task - Daniel J. Upton; Peter G. Enticott; Rodney J. Croft; Nicholas R. Cooper; Paul B. Fitzgerald (Experimental Brain Research, 2010)

Phylogenetic placement of the sugarcane orange rust pathogen Puccinia kuehnii in a historical and regional context - K. S. Braithwaite; B. J. Croft; R. C. Magarey; T. Scharaschkin (Australasian Plant Pathology, 2009)

RISK‐SENSITIVE ANTIPREDATOR BEHAVIOR IN THE TRINIDADIAN GUPPY, POECILIA RETICULATA - M. S. Botham; R. K. Hayward; L. J. Morrell; D. P. Croft; J. R. Ward; I. Ramnarine; J. Krause (Ecology, 2008)
The comparative approach has become a powerful tool for understanding how predation has shaped prey behavior. In this study we recorded the occurrence of common aquatic predator species and their densities in seven natural populations of Trinidadian guppies, Poecilia reticulata . We then exposed shoals of guppies from each of these populations to a series of predator treatments. Predator treatments differed in the species of predator used (pike cichlids, Crenicichla frenata ; rivulus, Rivulus hartii ; and freshwater prawns, Macrobrachium carcinus ) and thus in the level of risk posed. We recorded the antipredator responses of guppies in each of these predator treatments. The strength of antipredator behavior shown by guppies was affected by both the type of predator they were exposed to and the level of predation risk they experienced naturally in the wild. Importantly, we found that guppies from high‐risk populations showed a heightened response, compared to those from lower risk populations, only when exposed to the predator species that posed the greatest risk. Our results show the importance of individual predator species in shaping the behavioral traits of prey species at the population level. This has implications for prey movement between habitats that are geographically close but differ greatly in predator fauna.

D1-arginine257 mutants (R257E, K, and Q) of Chlamydomonas reinhardtii have a lowered QB redox potential: analysis of thermoluminescence and fluorescence measurements - Stuart Rose; Jun Minagawa; Manfredo Seufferheld; Sean Padden; Bengt Svensson; Derrick R. J. Kolling; Antony R. Crofts; Govindjee (Photosynthesis Research, 2008)

Sugarcane smut in Queensland: arrival and emergency response - B. J. Croft; R. C. Magarey; P. G. Allsopp; M. C. Cox; T. G. Willcox; B. J. Milford; E. S. Wallis (Australasian Plant Pathology, 2008)

Social network theory in the behavioural sciences: potential applications - J. Krause; D. P. Croft; R. James (Behavioral Ecology and Sociobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Numerical simulation of sea and bay breezes in a weak shear environment - D. Lu; L. White; R. S. Reddy; P. J. Croft; J. M. Medlin (Meteorology and Atmospheric Physics, 2006)

Phloem Alkaloid Tolerance Allows Feeding on Resistant Lupinus angustifolius by the Aphid Myzus persicae - Yasmin J. Cardoza; Shao Fang Wang; Jenny Reidy-Crofts; Owain R. Edwards (Journal of Chemical Ecology, 2006)

Social structure and co-operative interactions in a wild population of guppies (Poecilia reticulata) - D. P. Croft; R. James; P. O. R. Thomas; C. Hathaway; D. Mawdsley; K. N. Laland; J. Krause (Behavioral Ecology and Sociobiology, 2006)

Recent advances in the molecular biology of Leifsonia xyli subsp. xyli , causal organism of ratoon stunting disease - S. M. Brumbley; L. A. Petrasovits; S. R. Hermann; A. J. Young; B. J. Croft (Australasian Plant Pathology, 2006)

The effects of dexamphetamine on simulated driving performance - B. Y. Silber; K. Papafotiou; R. J. Croft; E. Ogden; P. Swann; C. Stough (Psychopharmacology, 2005)

Assortative interactions and social networks in fish - D. P. Croft; R. James; A. J. W. Ward; M. S. Botham; D. Mawdsley; J. Krause (Oecologia, 2005)

Miltefosine (Impavido): the first oral treatment against leishmaniasis - H. Sindermann; S. L. Croft; K. R. Engel; W. Bommer; H. J. Eibl; C. Unger; J. Engel (Medical Microbiology and Immunology, 2004)

Chronic MDMA (ecstasy) use, cognition and mood - K. McCardle; S. Luebbers; J. D. Carter; R. J. Croft; C. Stough (Psychopharmacology, 2004)

The Q-cycle – A Personal Perspective - Antony R. Crofts (Photosynthesis Research, 2004)

Social networks in fish - J. Krause; D. Croft; R. James (Journal of Fish Biology, 2003)
Social network theory underwent rapid development in the 1970s by sociologists and was recently further refined by physicists. Network theory has been applied to systems consisting of interconnected components as different as that of actors in Hollywood, the neural network of the nematode worm Caenorhabditis elegans , and the US national power grid. Network theory has great potential as a conceptual tool, for example, it can be used to provide quantitative predictions regarding information transmission, spreading of diseases, and the potential for establishing reciprocal altruistic relationships. Conventionally behavioural studies have been restricted to the analysis of social interactions between isolated pairs or small groups of individuals. Here we built up, however, from pair‐wise interactions, the social network of an entire population of guppies ( Poecilia reticulata ) in Trinidad. We show that guppies have highly structured social networks with significant repeated interactions between male–male, female–female and male–female pairs. Furthermore, sexual segregation within the network is positively correlated with the strength of the social interactions. Finally, individuals were observed to be more variable in their inter‐sexual interactions than their intra‐sexual ones.

Comparison of a Commercial Reversed Passive Latex Agglutination Assay to an Enzyme Immunoassay for the Detection of Shiga Toxin-Producing Escherichia coli - K. C. Carroll; K. Adamson; K. Korgenski; A. Croft; R. Hankemeier; J. Daly; C. H. Park (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

The use of a ‘phantom scalp’ to assess the possible direct pickup of mobile phone handset emissions by electroencephalogram electrode leads - A. W. Wood; D. L. Hamblin; R. J. Croft (Medical & Biological Engineering & Computing, 2003)

Development of PCR-based markers for detection of Leifsonia xyli subsp. xyli in fibrovascular fluid of infected sugarcane plants - P. W. J. Taylor; L. A. Petrasovits; R. Van der Velde; R. G. Birch; B. J. Croft; M. Fegan; G. R. Smith; S. M. Brumbley (Australasian Plant Pathology, 2003)

Population differentiation of Potamogeton pectinatus in the Baltic Sea with reference to waterfowl dispersal - R. A. King; R. J. Gornall; C. D. Preston; J. M. Croft (Molecular Ecology, 2002)
Forty populations of Potamogeton pectinatus L. were sampled from around the Baltic Sea basin. Analysis of 62 ISSR ‘loci’ showed that the number of clones per population is very variable but shows a tendency to decrease with latitude. Analysis of molecular variance revealed that, overall, just over half the variability is stored within populations and just under half between them (φ ST 0.496). In pairwise comparisons, most populations are significantly differentiated. Genetic distance between populations, as measured by φ ST , increases with geographical distance. Levels of population differentiation, however, are lower on the southeastern Swedish coast than elsewhere, a reduction correlated with the importance of this area as a staging post for the massive migrations of waterfowl from arctic Russia and western Siberia. Cumulative plots of φ ST against geographical distance along this coast suggest that, although it does not prevent significant population differentiation, bird traffic reduces it over distances of 150–200 km.